Subfamily-specific fluorescent probes for cysteine proteases display dynamic protease activities during seed germination - Lu, H; Chandrasekar, B; Oeljeklaus, J; Misas-Villamil, J; Wang, Z; Shindo, T; Bogyo, M; Kaiser, M; van der Hoorn, R (American Society of Plant Biologists, 2015)
Cysteine proteases are an important class of enzymes implicated in both developmental and defense-related programmed cell death and other biological processes in plants. Because there are dozens of cysteine proteases that are posttranslationally regulated by processing, environmental conditions, and inhibitors, new methodologies are required to study these pivotal enzymes individually. Here, we introduce fluorescence activity-based probes that specifically target three distinct cysteine protease subfamilies: aleurain-like proteases, cathepsin B-like proteases, and vacuolar processing enzymes. We applied protease activity profiling with these new probes on Arabidopsis (Arabidopsis thaliana) protease knockout lines and agroinfiltrated leaves to identify the probe targets and on other plant species to demonstrate their broad applicability. These probes revealed that most commercially available protease inhibitors target unexpected proteases in plants. When applied on germinating seeds, these probes reveal dynamic activities of aleurain-like proteases, cathepsin B-like proteases, and vacuolar processing enzymes, coinciding with the remobilization of seed storage proteins.